Remedying unemployment through affirmative development : the validation of the prediction model and qualitative assessment of an employment accelerator programme - De Kok, Marinus Bertus (Stellenbosch : Stellenbosch University, 2019)
Thesis (MCom)--Stellenbosch University, 2019.